Introduction to wireless and mobile systems - Agrawal, Dharma P.; Zeng, Qing-An. ([S.l.] : CL Engineering, 2007)
This text explains the general principles of how wireless systems work, how mobility is supported, what is the underlying infrastructure and what interactions are needed among different functional components. Designed as a textbook appropriate for undergraduate or graduate courses in Computer Science, Electrical Engineering, and Electrical and Computer Engineering, it focuses on qualitative descriptions and the realistic explanations of relationships between wireless systems and performance parameters. Rather than offering a thorough history behind the development of wireless technologies or an exhaustive list of work being carried out, the authors help EE and CSE students learn this exciting technology through relevant examples such as understanding how a cell phone starts working as soon as they get out of an airplane.
Keywords: Mobile communication systems; Wireless communication systems